The Business Judgment Rule in the Context of Directors’ Liability: A Comparative Study of the United States, Canada, and Indonesia: Business Judgment Rule dalam Perspektif Pertanggungjawaban Direksi: Studi Perbandingan Amerika Serikat, Kanada, dan Indonesia - Sanyoto, Alicia Andromeda; Lie, Gunardi (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Directors hold a strategic role in corporate governance, yet not all business decisions generate profits, exposing them to potential personal liability. Specific background: Differentiating reasonable business risks from negligence or bad faith remains a legal challenge across jurisdictions. Knowledge gap: Although the Business Judgment Rule, BJR, aims to protect directors who act prudently, in good faith, and based on adequate information, its formulation and judicial application differ significantly in the United States, Canada, and Indonesia, with Indonesia showing limited and inconsistent enforcement. Aims: This study analyzes the regulation and implementation of BJR in the three jurisdictions to evaluate how each balances managerial discretion and legal accountability. Results: The United States applies BJR as a strong presumption safeguarding informed and loyal decisions, Canada emphasizes judicial restraint based on the fairness of the decision-making process, and Indonesia codifies BJR principles but lacks clear evaluative standards in practice. Novelty: The study provides a comparative understanding of doctrinal and structural differences that shape the scope of director protection. Implications: Strengthening BJR interpretation and judicial guidelines in Indonesia is crucial to prevent hindsight bias, support responsible risk-taking, and enhance legal certainty in corporate governance. Highlights: The Business Judgment Rule protects directors who act in good faith, prudently, and with adequate information. The United States and Canada apply BJR through strong judicial restraint, while Indonesia’s application remains limited. Clearer BJR standards in Indonesia are essential to reduce hindsight bias and strengthen corporate governance. Keywords: Business Judgment Rule, Directors’ Liability, Comparative Corporate Law, Fiduciary Duty, Legal Accountability.